Collaboration and technology : 24th International Conference, CRIWG 2018, Costa de Caparica, Portugal, September 5-7, 2018, Proceedings /: 24th International Conference, CRIWG 2018, Costa de Caparica, Portugal, September 5-7, 2018, Proceedings. (2018) - Unknown
No abstract available